Study on failure maps of laser-welded I-core sandwich plates - Saffirna, Mohd Soffie Suppiah (2022)
This thesis focuses on failure maps of laser-welded I-core sandwich plates. Due to the area of its application, the sandwich plate used in ship structures considers the lightweight feature. Many different topologies can be explored but I-core carries an in-plane load suitable for bending testing. The PVC foam with closed-cell and low-density physical features, increases the strength and stiffness of sandwich plate. Laser welding is a common method for joining metal parts together. This thesis intends to analyze geometrical influence parameters, to conduct parametric studies on 3-point bending for various topics through simulation work, and finally, to develop failure maps of I-core sandwich plates. The tests were carried out on 48 I-core sandwich plates. Through the 3-point bending test, geometrical characteristics such as the use of PVC foam, the number of cores, and T-joint contact were observed. The second objective was carried out through simulation. This was accomplished by similar and dissimilar material properties, T-joint contact relationships, and weld widths. Overall, the results showed that using PVC foam infilled with I-core solved the problem of local weakness in areas where cores were missing. The A characteristic is ideal, the B characteristic is eccentric with no rootgap, the C characteristic is centric with a rootgap, and the D characteristic is eccentric with a rootgap. These characteristics is the failure occur at the T-joint contact. Observation of T-joint weld characteristics determined that A is the preferred welding method. As it has no rootgap and height penetration occurs at the center, it gives 815.20 N in the experimental result. Work on various materials on either faceplate or I-core portion yielded substantial results. When steel is used as the core and aluminum is used as the faceplate, the sandwich plate’s rigidity is reduced. The influence of rootgap and no rootgap was then examined, concluding that the absence of rootgap results in greater strength than the presence of rootgap. The greater the thickness of the weld, the greater the strength produced. The failure maps are provided in the thesis to explain the data accumulated. The area without cores could not bear the force, resulting in core detachment. The area known as weakness is improved by increasing the number of cores. In practice, the use of I-cores and PVC foam provides mechanical support for the faceplate. Finally, the project achieved the objectives of this thesis. The use of I-cores and PVC foam infilled to strengthen the sandwich is a good approach. The failure mode was observed until deformation occurred, and the type of failure mode was determined. The methodologies for 3-point bending simulation were performed in Abaqus software. In comparison to different materials on the faceplate and I-core, the first analysis determined that using strong materials on both components improved the elastic stiffness by 1.83 kN/mm. The results of the second analysis showed that the presence of a rootgap at the contact surface caused debonding. The final study concluded that a wholesome T-joint could not be achieved effectively; thus, it is advisable to assume that the weld length is close to the core length.